Report on the Observance of Standards and Codes : Corporate Governance Country Assessment, Panama - World Bank (Washington, DC, 2013)
This report provides an assessment of the corporate governance policy framework and enforcement and compliance practices in Panama. Much progress has been made since the drafting of the new Securities and Banking Laws in the late 1990s. The major issues are driven by the preponderance of banks. Given abundant debt financing, there is little need for equity financing. In addition, institutional investors are largely absent from the equity market. The main legislation concerning listed companies is based on US laws and is sophisticated, though poorly enforced. The report recommends: (1) a sufficient level of disclosure in practice, to enable the identification of beneficial owners and their exact stakes, in the annual report; (2) simplified shareholder redress, including a more active role for the securities regulator, so as to enable shareholders to challenge corporate decisions; (3) the creation of an effective audit oversight mechanism; (4) the re-introduction of the regulation on proxy solicitation, requiring the provision of sufficient information for shareholders to make informed voting decisions; (5) mandatory audit committees for all listed companies; (6) clearer fiduciary duties and liabilities of directors, and (7) the availability of relevant and useful training for board members. The report also proposes strengthening the securities regulator's ability to issue and enforce regulations on listed firms, their boards and shareholders and stricter monitoring of the quality of disclosure.